Pharmacotherapy of hyperthyroidism in cats (ro.) - Andreea Pap; Romeo T. Cristina (Medicamentul Veterinar)
Currently, the feline hyperthyroidism possesses three types of treatment that includes medication, surgery and radioactive therapie. The success of these therapies consists in obtaining favorable results, by inhibiting thyroid hormone secretion, reducing clinical signs, improving the live's quality and by absence of side effects of administered medication. One of these three therapies that fulfill these conditions and considered ideal for clinicians is the radiation therapy. Choosing this therapy depends not only on the availability of radioiodine licensed clinics or the presence of a skilled surgeon but also on the patient's clinical condition, especially when a cardiovascular or renal disease is present in this review paper.